EXPERIMENTAL STRATEGY FOR IN VITRO EVALUATION OF CYTOTOXIC / ANTITUMOR PROPERTIES OF NEW METAL COMPLEXES WITH DIFFERENT LIGANDS - R. Alexandrova; R. Spasov; Z. Petrova; T. Zhivkova; L. Dyakova; D. Dinev; M. Glavcheva; B. Andonova-Lilova; A. Abudalleh; M. Georgieva; G. Miloshev; D.-C. Culita; et al. (Trakia Journal of Sciences)
PURPOSE. The aim of this study was to evaluate cytotoxic / antitumor properties of newly synthesized metal [Zn(II), Cu(II), Co(II), Ni(II), Zn(II)/Ag(I), Zn(II)/Au(I)] complexes with various ligands (Schiff bases, non-steroidal anti-inflammatory drugs, bile acids) and to introduce an optimized strategy for such investigations in our research activity. MATERIALS AND METHODS. Human and animal tumor and non-tumor cells were used as model systems. Short-term (3 – 96h) and long-term (> 2 weeks) experiments were carried out using cytotoxicity assays, cytological / immunocytochemical, biochemical and molecular-biological methods to assess the influence of the compounds on cell viability and proliferation and their ability to induce apoptosis/necrosis and/or autophagy. RESULTS. The examined metal complexes express cytotoxic activity that is time- and concentrationdependent and are more active than the corresponding ligands tested alone. Zn(II)/Au(I) and Zn(II)/Ag(I) complexes with Salen are found to be the most promising cytotoxic agents being effective also in multidrug resistant cancer cells. Their cytotoxic activity is higher than those of cisplatin, oxaliplatin and epirubicin. CONCLUSIONS. A complex approach, based on a wide range of cell cultures and methods with different molecular / cellular targets and mechanisms of action was optimized and successfully applied for the assessment of cytotoxicity of new metal complexes.